The neutrophil-to-lymphocyte ratio as a new prognostic factor in cancers: a narrative review - Heshmat-Ghahdarijani, Kian; Sarmadi, Vida; Heidari, Afshin; Falahati Marvasti, Alireza; Neshat, Sina; Raeisi, Sina (Frontiers in Oncology, 2023)
The increasing incidence of cancer globally has highlighted the significance of early diagnosis and improvement of treatment strategies. In the 19th century, a connection was made between inflammation and cancer, with inflammation recognized as a malignancy hallmark. The neutrophil-to-lymphocyte ratio (NLR), calculated from a complete blood count, is a simple and accessible biomarker of inflammation status. NLR has also been proven to be a prognostic factor for various medical conditions, including mortality classification in cardiac patients, infectious diseases, postoperative complications, and inflammatory states. In this narrative review, we aim to assess the prognostic potential of NLR in cancer. We will review recent studies that have evaluated the association between NLR and various malignancies. The results of this review will help to further understand the role of NLR in cancer prognosis and inform future research directions. With the increasing incidence of cancer, it is important to identify reliable and accessible prognostic markers to improve patient outcomes. The study of NLR in cancer may provide valuable insights into the development and progression of cancer and inform clinical decision-making.